Development and Validation of Scale to Measure Risk Orientation of Farmers - Priti Priyadarshni , Shantanu Rakshit and R. N. Padaria, (Indian Journal of Extension Education, 2017)
Understanding the preferences and aversion of famers towards risks in agriculture and their behaviour regarding adoptionand rejection of risk adjustment technologies is essential for devising any extension strategy. An effort was made in thisstudy to develop a scale to measure risk orientation of farmers using Thurs tone's Equal-Appearing Interval (EAI)technique. Apool of 36 statements was selected on basis of 4 levels of systemic risk as mentioned by OECD (2009). Thesestatements were administered to experts on a 9-point continuum. Based upon the scale values and inter quartile range, 19statements were selected. The scale was found to have a reliability coefficient of 0.80, which was obtained by split-halfmethod followed by correction using Spearman Brown Prophecy formula. Scalogram analysis with Goodenoughtechnique revealed a coefficient of reproducibility of 0.80 showing unidimensionality of the scale. Further theindependent criteria (Technonet Asia scale of risk taking ability,1981) based validity assessment showed a significantcorrelation of 0.713. The final scale comprising of 19 statements was used to measure the risk orientation of the farmers